2020
DOI: 10.21014/acta_imeko.v9i4.754
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing and technical strategies for improving outcomes in breast reconstructive surgery

Abstract: It has been widely reported that breast reconstruction improves the quality of life of women who undergo mastectomy for breast cancer. <br />This approach provides many psychological advantages. Today, different techniques are available for the breast oncoplastic surgeon <br />that involve the use of breast implants and autologous tissues, also offering interesting results in terms of aesthetic and patient-reported <br />outcomes. On the other hand, advanced technologies and design strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Several strategies have become widespread to support healthcare managers in increasing knowledge from data. Health technology assessment (Improta et al, 2009;Improta et al, 2012), smart technologies (Apicella et al, 2021;Arpaia et al, 2020;Rocco et al, 2020;Angrisani et al, 2020;Bernasconi et al, 2020), specific care path (Improta et al, 2021;Improta et al, 2020), data analysis (Ponsiglione et al, 2022;Improta et al, 2014;Ponsiglione et al, 2021a;Cesarelli et al, 2012;Cortesi et al, 2019) and machine learning (Improta et al, 2022;Ponsiglione et al, 2021b) are just a few examples.…”
Section: Lean Application In Healthcarementioning
confidence: 99%
“…Several strategies have become widespread to support healthcare managers in increasing knowledge from data. Health technology assessment (Improta et al, 2009;Improta et al, 2012), smart technologies (Apicella et al, 2021;Arpaia et al, 2020;Rocco et al, 2020;Angrisani et al, 2020;Bernasconi et al, 2020), specific care path (Improta et al, 2021;Improta et al, 2020), data analysis (Ponsiglione et al, 2022;Improta et al, 2014;Ponsiglione et al, 2021a;Cesarelli et al, 2012;Cortesi et al, 2019) and machine learning (Improta et al, 2022;Ponsiglione et al, 2021b) are just a few examples.…”
Section: Lean Application In Healthcarementioning
confidence: 99%
“…68 Another interesting application of developing customized 3D scaffolds using poly(e-caprolatone) with tailored morphology (with a length of 7 mm, width of 7 mm and a height of 8 mm, a filament distance of 650 mm and different internal quadrangular, complex polygonal and triangular pore geometries, 0°/90°, 0°/ 60°/120°, and 0°/45°/90°/135°lay down patterns), based on 3D additive manufacturing has been described. 69 The variation in pore size geometries within a single scaffold is said to promote tissue regeneration by providing the required strength and flexibility. 70 3D structures with tailored architectures of varying lay-down patterns, pore geometries thereby aid in breast reconstructive surgery.…”
Section: Biomedical Applications Of Uv Based 3d Printed Biomaterialsmentioning
confidence: 99%
“…The researchers conducted preliminary mechanical and biological analyses to see how the lay-down pattern affected the performances of the fabricated devices. The results demonstrated that the constructions with a 0°/90° pattern gave a compressive modulus that was much higher than those obtained for the other types of scaffolds at a fixed filament diameter, filament spacing, and slice thickness [ 18 ].…”
Section: Introductionmentioning
confidence: 99%